Decision Trees for a Virtual Supply Chain - Trzpiot, Grażyna; Ganczarek-Gamrot, Alicja (Drzewa decyzyjne w analizie wirtualnych łańcuchów dostaw, 2009)
The aim of this article is to measure the influence of logistic competences and the transport on the development of a virtual supply chain for different groups of enterprises from the Silesian region, Poland. Moreover, we propose actions enabling the effective formation of virtual supply chains in the enterprise. Based on the results of the survey of Silesian businesses having significant influence on the regional development and the competitiveness of the economy, a statistical analysis of decisions taken in the field of logistics was carried out by applying the decision trees technique. Key words: Silesian businesses, virtual supply chain, decision trees
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 65, s. s. 92-104
Keywords: Silesian businesses; virtual supply chain; decision trees